2013
DOI: 10.1097/ico.0b013e3182930b1d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diquafosol Sodium Eye Drops on Tear Film Stability in Short BUT Type of Dry Eye

Abstract: DQS improved subjective symptoms and prolonged BUT in eyes with UTF not associated with low tear secretion and ocular surface epithelial damage. Because many patients who have UTF are refractory to conventional treatments, DQS may offer benefits in the treatment of dry eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
(23 reference statements)
0
46
0
Order By: Relevance
“…Two studies compared 3% diquafosol with preservative-free artificial tears [17, 19]. One study examined 0.9% normal saline [11] and 1 study used placebo eye drops [15].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies compared 3% diquafosol with preservative-free artificial tears [17, 19]. One study examined 0.9% normal saline [11] and 1 study used placebo eye drops [15].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports suggested that short BUT-type dry eye is associated with allergic conjunctivitis 43 and a decreased mucin level in tear fluid. 44 In fact, this case was complicated with perennial allergic conjunctivitis, so the manifestation of this case might have been caused by allergic conjunctivitis rather than lacrimal gland dysfunction. Diquafosol ophthalmic solution reportedly is effective in improving short BUTtype dry eye, 44 and this case also responded well to the Figure 4 Slit-lamp photographs of the right eye of a 54-year-old female with aqueous tear-deficient dry eye with SS.…”
Section: Discussionmentioning
confidence: 99%
“…44 In fact, this case was complicated with perennial allergic conjunctivitis, so the manifestation of this case might have been caused by allergic conjunctivitis rather than lacrimal gland dysfunction. Diquafosol ophthalmic solution reportedly is effective in improving short BUTtype dry eye, 44 and this case also responded well to the Figure 4 Slit-lamp photographs of the right eye of a 54-year-old female with aqueous tear-deficient dry eye with SS. The fluorescein staining of the cornea and conjunctiva was markedly improved at 6 and 12 months after the start of the treatment with 3% diquafosol ophthalmic solution in comparison to at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Topical instillation of DQS ophthalmic solution is reportedly effective for various types of dry eye, including aqueous tear-deficient dry eye 38 with a Schirmer test value of ≤ 5 mm (eg, SS), short BUT type dry eye, 39 dry eye after surgery, [40][41][42] and obstructive meibomian gland dysfunction. 43 The possible mechanism of that action is that DQS ophthalmic solution increases tear-film stability, thus eliminating the vicious cycle (the core mechanism of dry eye on the ocular surface) by increasing fluid secretion, mucin secretion, and membrane-binding mucin gene expression.…”
Section: Discussionmentioning
confidence: 99%